2020
DOI: 10.3390/biom10101388
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Human PD-L1 Nanobody for Immuno-PET Imaging: Validation of a Conjugation Strategy for Clinical Translation

Abstract: Immune checkpoints, such as programmed death-ligand 1 (PD-L1), limit T-cell function and tumor cells use this ligand to escape the anti-tumor immune response. Treatments with monoclonal antibodies blocking these checkpoints have shown long-lasting responses, but only in a subset of patients. This study aims to develop a Nanobody (Nb)-based probe in order to assess human PD-L1 (hPD-L1) expression using positron emission tomography imaging, and to compare the influence of two different radiolabeling strategies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 32 publications
3
59
0
Order By: Relevance
“…Optimally this nanobody needs to be labeled with a short-lived PET-isotope such as 68 Ga or 18 F using new or established radiochemistry procedures (25,(41)(42)(43). Extrapolating from our still ongoing clinical trials with a 68 Ga-labeled anti-HER2 nanobody breast cancer PET-tracer ( 26) and an anti-CD206 nanobody macrophage PET-tracer (25), we are hopeful that the future clinical anti-LAG-3 nanobody PET-tracer will also be safe, sensitive and will conveniently provide a whole-body picture of LAG-3 expression levels in a same-day imaging procedure with acceptable dosimetry levels.…”
Section: Discussionmentioning
confidence: 99%
“…Optimally this nanobody needs to be labeled with a short-lived PET-isotope such as 68 Ga or 18 F using new or established radiochemistry procedures (25,(41)(42)(43). Extrapolating from our still ongoing clinical trials with a 68 Ga-labeled anti-HER2 nanobody breast cancer PET-tracer ( 26) and an anti-CD206 nanobody macrophage PET-tracer (25), we are hopeful that the future clinical anti-LAG-3 nanobody PET-tracer will also be safe, sensitive and will conveniently provide a whole-body picture of LAG-3 expression levels in a same-day imaging procedure with acceptable dosimetry levels.…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1-targeting antibody fragments have recently been developed and used to generate high-contrast images of tumors with varying levels of PD-L1 expression [ 92 , 93 , 94 ]. Four high-affinity anti-PD-L1 nanobodies were radiolabeled with 99m Tc, and evaluated for preclinical SPECT/CT imaging of PD-L1 in syngeneic mice [ 92 ].…”
Section: Nanobodies As a Tool For Imaging Cancermentioning
confidence: 99%
“…Due to the outstanding features, such as fast blood clearance, deep tissue penetration, and high a nity, sdAbs are identi ed as ideal candidates for nuclear medicine applications [16,17]. Several studies have demonstrated the safety and feasibility of radiolabeled sdAbs for cancer diagnosis and treatment [18][19][20][21][22][23][24][25][26]. In our previous study, we reported a 99m Tc-labeled antiprogrammed death ligand-1 (PD-L1) sdAb as a SPECT/CT tracer for PD-L1 expression in non-small cell lung cancer (NSCLC) [26].…”
Section: Introductionmentioning
confidence: 99%